Happy kinsenas! online shopping as an emotion regulation strategy among Filipino working adults - Managbanag, Louie Jay S.; Onde, Weyvin Maury G.; Zamora, Ma. Ceane Jane N. (2023)
This study explores the online shopping experiences and emotion regulation strategies of Filipino working adults. The emotional dimension of online shopping as an emotion regulation strategy is examined, along with its implications for consumer behavior. Thematic analysis revealed that emotions, such as happiness and excitement, influenced participants' likelihood of making online purchases. However, these positive emotions sometimes led to maladaptive behaviors, such as impulsive buying. Participants also employed the add-to-cart feature to delay gratification and alleviate negative moods. Online shopping could induce negative emotions, including frustration and regret, particularly influenced by certain features of online platforms. Cognitive distortions, such as catastrophizing and 'should' statements, hindered effective decision-making. Participants exhibited rationality in purchase decisions, considering factors such as incentives, desirability, trustworthiness, quality, and financial resources. However, cognitive distortions also affected decision-making, leading to unreasonable or impulsive behaviors. The study aknowledges limitations, including the exclusive focus on Filipino working adults, cross-sectional design, and limited exploration of contextual factors. Findings emphasize the importance of digital emotion regulation regulation strategies to mitigate negative emotions during online shopping. This research provides insights for enhancing the online shopping experience and promoting informed decision-making. Future research directions including investigation underlying psychological mechanisms and long-term effects of online shopping as a coping mechanism.